2019
DOI: 10.1038/s41598-018-37476-9
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of syndecans to cellular internalization and fibrillation of amyloid-β(1–42)

Abstract: Intraneuronal accumulation of amyloid-β(1–42) (Aβ1–42) is one of the earliest signs of Alzheimer’s disease (AD). Cell surface heparan sulfate proteoglycans (HSPGs) have profound influence on the cellular uptake of Aβ1–42 by mediating its attachment and subsequent internalization into the cells. Colocalization of amyloid plaques with members of the syndecan family of HSPGs, along with the increased expression of syndecan-3 and -4 have already been reported in postmortem AD brains. Considering the growing eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
130
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(143 citation statements)
references
References 81 publications
2
130
0
Order By: Relevance
“…Our related studies with non-viral drug delivery agents, including cell-penetrating peptides (CPPs) and cationic liposomes, contributed to the understanding of SDCs' capacity to deliver bioactive macromolecules into the cells 43,44,64 . Moreover, we also revealed that SDCs contribute to the seeding and prion-like spreading of pathological protein aggregates, the major molecular culprits responsible for the onset of neurodegenerative disorders 45,46 . During these endeavors, we have been developing several SDC speci c assays and constructs, enabling thorough analyses of SDCs' interactions with potential ligands.…”
Section: Development Of E Cient Therapeutics Against Covid-19 Is Hampmentioning
confidence: 86%
See 4 more Smart Citations
“…Our related studies with non-viral drug delivery agents, including cell-penetrating peptides (CPPs) and cationic liposomes, contributed to the understanding of SDCs' capacity to deliver bioactive macromolecules into the cells 43,44,64 . Moreover, we also revealed that SDCs contribute to the seeding and prion-like spreading of pathological protein aggregates, the major molecular culprits responsible for the onset of neurodegenerative disorders 45,46 . During these endeavors, we have been developing several SDC speci c assays and constructs, enabling thorough analyses of SDCs' interactions with potential ligands.…”
Section: Development Of E Cient Therapeutics Against Covid-19 Is Hampmentioning
confidence: 86%
“…SDCs share a similar structure: a one-span and highly conserved transmembrane domain (TM) and a relatively short cytoplasmic domain (CD) 43,44 . The extracellular domain (ectodomain) of SDCs is more diverse, containing HS attachment sites with glycosaminoglycan (GAG) side chains 45,46 .…”
Section: Development Of E Cient Therapeutics Against Covid-19 Is Hampmentioning
confidence: 99%
See 3 more Smart Citations